(untitled) (Anwer Khan Modern Medical College Journal, 2018)
Background: EF is an important measurement in determining how well the heart is pumping out blood and in diagnosing as well as tracking the heart failure (HF). Normal EF varies at 55% to 70%, while EF 40% to 55% may indicate damage perhaps from previous heart attack, but may not indicate HF. However, measurement under 40% may show evidence of HF or cardiomyopathy and patient with EF< 35% may be at the risk of life threatening irregular heartbeats. Such patients are considered to be at high risk for anaesthesia as life threatening irregular heartbeats lead to sudden cardiac arrest and sudden death. Objectives: The aim of this study was to find out the characteristics of patients, identifying of the risk factors, better understanding of pathophysiology, pre-operative optimization of the patients, uses of stable drugs & anesthetic techniques, reduces intraoperative or early postoperative complications & perioperative morbidity, mortality. Methods: In this retrospective study we described our experiences of 236 cases of very low ejection fraction (20% - 35%) from 1st July 2014 - 30th June 2017. We reviewed their medical history and noted age, sex, type of operation & anesthesia, pattern of operation either elective or emergency, preoperative investigation and preparation, as well as details of anaesthetic management, were also recorded. Results: General anaesthesia was performed in 176 (74.58%) cases and rest of 60(25.42%) cases were regional where spinal 42(17.80%) cases & epidural 18(7.62%) cases. The age of the patients were in the range of 20 to 70 years, with majority of the patients were in 60 to 69 years age group. The majority of the patients about 46.19% were in LVEF 26 - 30% group, 36.01% patients were in 31 - 35% group and rest of 17.80% patients were in 20 - 25% group. Average duration of operation incase of general anesthesia 66.5(±2.28SD) min and incase of regional 44.2(±3.25SD) min. The mortality rate only 1.27%. Conclusions: Preoperative patient optimization, intraoperative haemodynamic stability and postoperative care have contributed to the success of very low ejection fraction patients in our hospital. Anwer Khan Modern Medical College Journal Vol. 9, No. 2: Jul 2018, P 114-120